2015
DOI: 10.5530/ijopp.7.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ADRs and Associated Factors of Antiretroviral Treatment on HIV Positive Adults at Jush

Abstract: A cross sectional study is designed to assess the prevalence of adverse drug reactions and its associated factors on who are already under Highly Active Antiretroviral Therapy. Considerable progress has been made to access the therapy since the decades, even though; currently five million people do not have an access to HIV therapy, it just represents 35% only. The objective of present research is to assess the prevalence of ADRs and its associated factors on HAART at Jimma University Specialized Hospital. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…This is consistent with research conducted in Ethiopia and Ghana [21,4]. In contrast to these findings, a study in HIV infected patients at an ART Centre of tertiary care hospital in India showed a higher prevalence in males than in females [22].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…This is consistent with research conducted in Ethiopia and Ghana [21,4]. In contrast to these findings, a study in HIV infected patients at an ART Centre of tertiary care hospital in India showed a higher prevalence in males than in females [22].…”
Section: Discussioncontrasting
confidence: 54%
“…Further, it has been reported that up to 80 % of HIV -infected patients experience ADRs during their therapy, presumably as a result of immune dysregulation, altered drug metabolism and/or drug interactions [21].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Jimma University specialized hospital, Ethiopia, on HIV patients under highly active antiretroviral therapy (HAART) showed that 70.8% of them had developed ADRs [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Ethiopia despite the potential risks of adverse drug reactions, to date there are about 600 ADR cases reported per year to the national pharmacovigilance center. The available reports at the national medicine regulatory authority are very low as compared to the World Health Organization's recommended adverse drug reaction reporting rate, which is 200 reports per million population per year [20,21,[24][25][26][27]. Adverse drug reaction reporting experiences among medical doctors in Addis Ababa are not well known and the reasons are not properly explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation